SOSIALISASI PENTINGNYA PENDIDIKAN INOVASI TEKNOLOGI PEMBELAJARAN - Hetwi Marselina Saerang; Harol R. Lumapow; Viktory Nicodemus Joufree Rotty (LPPM Universitas Bina Bangsa, 2023)
Changes in the use of technology are taking place in the world of education. There are three main changes currently taking place, namely (1), the emergence of extensive (broad) use of technology, (2), the transition to the use of technology from elementary schools to high schools, (3), the introduction of a national curriculum using the Information Communication system and Technologies” (ICT). Innovation can be thought of as having a cycle with four phases: (1), idea generation and invention; (2), idea selection; (3), implementation of ideas; and (4), the diffusion of ideas (Eggers & Singh, 2019). Innovation offers benefits and can include the introduction of knowledge. Hence how do people see the word 'innovation' in education, as Norton (2013:1) argues that “more innovation needs to be encouraged in education so that students can benefit from new technologies through face-to-face and online approaches; or Innovation High School (2012: 1) states that